Distribusi Pendapatan Rumah Tangga Nelayan (Studi Kasus Di Desa Sungai Bakau Kecamatan Seruyan Hilir Timur dan Desa Sungai Undang Kecamatan Seruyan Hilir Kabupaten Seruyan) - Lili Winarti; Rokhman Permadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
The objectives of this research were to analyze distribution of fishermen household incomes in Sungai Bakau village in Seruyan Hilir Timur Distric and Sungai Undang in Seruyan Hilir Distric of Seruyan Regency. The methode of this research applied survey method using questioners to gather primary data, the number of respondent in this study is 157 people consisting of fishermen in the village Sungai Bakau 70 people and in the village Sungai Undang 87 people. to analyze distribution of family incomes using coefficient Gini Ratio. The result of the descriptive analysis of the family consumption expenditure  in the village of Sungai Bakau and Sungai Undang shows that household expenditure allocated for food consumption is greater than in the non-food consumption. people's income distribution reflected in the Gini Ratio 0.18197 for Sungai Bakau village and 0.20905 for Sungai Undang, this condition indicated a level of inequality low.